PENSERTIPIKATAN TANAH ULAYAT (PUSAKO TINGGI) MINANGKABAU DENGAN PENDAFTRAN TANAH SISTEMATIS LENGKAP (PTSL) - Sri Armadani; Syafrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Customry law and national law, in complete syestematic land registration, to the impect of certifitation. Communal land (High Pusako) in Minangkabau will cause various impacts, because it is not in accordance with the laws of the Minangkabau customary land. Problem formulation, how the impact of the system of inheritance of Minangkabau communal land after land titling by PTSL and what are the social and cultural impacts of Minangkabau law after PTSL certifitation of communal land. The purpose of this study was to find out how the system of inheritance of traditional land the PTSL certification and know the impact of the PTSL ownership of customary land on the social culture and law of Minangkabau. this study uses descriptive qualitative research methods, with 6 research subjects. From the results of in-depth interviews and observations in the field, that communal land does not have a certificate. If it is certified communal land (high pusako) private rights, not the people anymore. In certification of Minangkabau communal land there is no element of compulsion must meet various special requirements in west Sumatera, the deliberation decision in one clan was decided by the head of the inheritance mamak and known by the local customary leader. And other special conditions, namely genealogy for at least three generations. The positive impact of the certification of communal land is national legal certainty, reducing conflict, the price of land becomens expensive, and the nagative impact caused by the waning of customary and cultural law to conflict. It can be concluded that registration of customary land has no coercion from the national land agency and the requirements for submitting certificates are different from other regions besides West Sumatera.Keywords: Land, Communal, PTSL, Registration, Law, Custom, MinangkabauJOM